2010
DOI: 10.1111/j.1365-3180.2010.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of post‐emergence weed harrowing

Abstract: Rasmussen J, Mathiasen H & Bibby BM (2010). Timing of post‐emergence weed harrowing. Weed Research50, 436–446. Summary The timing of post‐emergence weed harrowing was evaluated for two years in spring barley with crop‐weed selectivity and crop recovery as the key parameters measured. Selectivity describes the relationship between weed control and crop soil cover immediately after harrowing, with crop soil cover as the percentage of the crop that has been covered by soil due to harrowing. Crop recovery describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…In cases of high weed competition and denser soils, nearly 45% crop soil cover was necessary to achieve 80% weed control [16]. In contrast, other studies suggested a maximum of about 25% crop soil cover [13]. However, higher degrees of crop soil cover than 25% resulted in 3% to 45% yield gain in case of high weed competition, and in cases of poor weed competition the yield loss effect due to harrowing was lower than 1% [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of high weed competition and denser soils, nearly 45% crop soil cover was necessary to achieve 80% weed control [16]. In contrast, other studies suggested a maximum of about 25% crop soil cover [13]. However, higher degrees of crop soil cover than 25% resulted in 3% to 45% yield gain in case of high weed competition, and in cases of poor weed competition the yield loss effect due to harrowing was lower than 1% [16].…”
Section: Resultsmentioning
confidence: 99%
“…Our proposed harrowing system is advantageous owing to two main reasons. Firstly, it integrates relationships between crop soil cover, weed control and yield increase as a result of harrowing, e.g., as suggested by Weis et al [1], and Rasmussen et al [13]. Secondly, the variables required to determine those relationships ( i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Pannacci and Tei (2014), summarising the results of eight field experiments on the mechanical weed control in the same area, showed an average weed control efficacy of 37% and 73%, for spring-tine harrow and split-hoeing respectively. Furthermore, other authors affirmed that for the inter-row cultivators the trade-off between weed control and crop damage is not significant and weeds are generally well managed by cultivation, while whole-crop cultivators, like springtine harrows show varying and sometimes poor results (Cirujeda and Taberner, 2006;Cloutier et al, 2007;Peruzzi et al, 2007;Van der Weide et al, 2008;Rasmussen et al, 2010). However, it should be point out as by an economical point of view the inter-row cultivators, like split-hoeing or traditional hoeing, seems to be less sustainable than whole-crop cultivators, like spring-tine harrowing.…”
Section: Articlementioning
confidence: 99%
“…Therefore, selectivity, which is usually characterised by the relationship between weed control and crop damage, is a key parameter in post-emergence weed harrowing (Rasmussen et al, 2008;RuedaAyala et al, 2011). Because of low selectivity, post-emergence weed harrowing may reduce crop yields, especially if weed competition is low, timing is unfavourable or implement setting is inappropriate (Rasmussen and Nørremark, 2006;Rasmussen et al, 2010). Studies shown that the primary action with post-emergence tine harrowing was burying plants (Kurstjens and Perdok, 2000), even if uprooting has been acknowledged to play a role with weakly anchored plants (Kurstjens and Kropff, 2001).…”
Section: Introductionmentioning
confidence: 99%